TEKNOLOGI, MODERNITAS, DAN ZAMAN ‘PANTJAROBA’: REPRESENTASI RADIO DALAM DUA ROMAN INDONESIA DI AKHIR ZAMAN KOLONIAL - Suryadi Suryadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
The reception and perception of the Indonesian society onradio technology in the early period of the appearance of thistechnology in the former Netherlands East Indies can of course betraced in its diverse culture texts, including the literary texts. Eventhough such technological invention as radio is an element that isquite apparent and give colour in many modern Indonesian literarytexts, this element has not seemed to attract the attention of scholarsof Indonesian literary studies. This paper looks at the images of radiotechnology in modern Indonesian literary texts by examining how thistechnology is represented as a matter of course in early modernIndonesian literary works. Two works which will be investigated in thisarticle are Muhammad Dimyati’s Dibalik Tabir Gelombang Radio(1940) and A. Damhoeri’s Zender Nirom (1940). In this paper, Idiscuss them in terms of the explicit presence of radio as an urbanicon and symbol of modernity.